Spatiotemporal availability of pollinator attractive trees in a tropical streetscape: unequal distribution for pollinators and people - Gomes, Ingrid N.; Bosenbecker, Camila; Silva, Victor H.D.; Cardoso, João C.F.; Pena, João C. [UNESP]; Maruyama, Pietro K. (Elsevier, 2023)
Street trees integrate the urban green infrastructure and are important elements for the maintenance of biodiversity, including pollinators. Thus, assessments of the spatiotemporal distribution and composition of these trees can subsidize strategies of conservation for different groups of pollinators in the cities. Here, we evaluated the spatiotemporal distribution of trees attractive to pollinators across the streetscape of a large Brazilian metropolis with more than 2.5 million inhabitants. We used the georeferenced data of ca. 300,000 woody plant individuals cataloged across the streetscape. These plants were characterized according to their geographical origin, flowering season, and the floral visitor groups that are attracted based on a literature survey. We also tested the “luxury effect” hypothesis on the resource availability to pollinators by evaluating the relationship between the average family income of the population and the richness and abundance of trees. We found that the streetscape was characterized by the dominance of a few tree species, with a balanced representation of both native and non-native species. Bees were the most favored group (94.86%) while bats (1.43%) and moths (1.73%) were the least. The potential supply of resources was homogeneous across dry and wet seasons, but the density of trees was reduced in most of the landscape. We found a strong luxury effect since tree richness and abundance were positively related to regions with higher average family income. Our study highlights the need for better planning and management practices of urban green areas to support pollinators more uniformly across streetscapes. This will allow the benefits provided by pollinators to be more evenly shared among residents of urban landscapes.
Keywords: Conservation; Green infrastructure; Luxury effect; Street trees; Tropical cities; Urban ecology